Whole genome profiling physical map and ancestral annotation of tobacco Hicks Broadleaf. (26th June 2013) - Sierro, Nicolas; van, Jan; van, Michiel J. T.; Martin, Florian; Stormo, Keith E.; Peitsch, Manuel C.; Ivanov, Nikolai V.
Summary Genomics‐based breeding of economically important crops such as banana, coffee, cotton, potato, tobacco and wheat is often hampered by genome size, polyploidy and high repeat content. We adapted sequence‐based whole‐genome profiling (WGP™) technology to obtain insight into the polyploidy of the model plant Nicotiana tabacum (tobacco). N. tabacum is assumed to originate from a hybridization event between ancestors of Nicotiana sylvestris and Nicotiana tomentosiformis approximately 200 000 years ago. This resulted in tobacco having a haploid genome size of 4500 million base pairs, approximately four times larger than the related tomato (Solanum lycopersicum) and potato (Solanum tuberosum) genomes. In this study, a physical map containing 9750 contigs of bacterial artificial chromosomes (BACs) was constructed. The mean contig size was 462 kbp, and the calculated genome coverage equaled the estimated tobacco genome size. We used a method for determination of the ancestral origin of the genome by annotation of WGP sequence tags. This assignment agreed with the ancestral annotation available from the tobacco genetic map, and may be used to investigate the evolution of homoeologous genome segments after polyploidization. The map generated is an essential scaffold for the tobacco genome. We propose the combination of WGP physical mapping technology and tag profiling of ancestral lines as a generally applicable method to elucidate the ancestral origin of genome segments of polyploid species. The physical mapping of genes and their origins will enable application of biotechnology to polyploid plants aimed at accelerating and increasing the precision of breeding for abiotic and biotic stress resistance.